Waste Management System at Bheri Hospital, Nepalgunj - Acharya, Lal Mani (Academia Research Journal, 2023)
The purpose of this research was to find out the present situation of the waste management system at Bheri Hospital in Nepalgunj. It also aimed to investigate the waste management knowledge and practices of various groups of people, including patients, visitors, hospital administrators, cleaning staff, and community members. The study was carried out to identify the hospital's waste disposal practices and to determine the impact of waste disposal on the health of the surrounding community. When selecting the hospital site for waste management practice, the researcher used a purposive sampling method. This research was descriptive in nature. The information was gathered from observations, and interviews. The total number of respondents for this study was 170. Among them were 20 hospital administrative personnel and 150 local residents who served as respondents. During the course of this research, 49.18 percent of respondents indicated that hospital product waste needed to be addressed. In terms of waste management practice, 60 percent of respondents responded by telling the researcher that it was satisfactory. In terms of hospital waste management, 53.33 percent of respondents said that it was the hospital administration's responsibility to handle waste materials properly. Similarly, 49.33 percent of the respondents said that hospital toilet were the most affected. Similarly, a survey found that 30.37 percent of respondents took precautions to avoid hazardous waste. Prior to collection, waste materials were classified as sharp, hazardous, and non-hazardous. The researcher discovered that the Hospital's waste management system was satisfactory based on observations. Similarly, waste handling personnel were observed using safety precautions throughout their shift. The researcher then discovered that the hospital disposed of the waste in its own compound. However, the waste collected had degraded natural aesthetics and polluted the environment. Overall, the waste management of the hospital was satisfactory. However, the hospital should implement safety measures and launch public awareness campaigns to ensure the safety of patients and residents in the surrounding community.